Current issues in the practical use of allopurinol in patients with gout and hyperuricemia - M. S. Eliseev (Современная ревматология)
The cornerstone of the treatment of gout and hyperuricemia (HU) is the use of urate-lowering drugs, primarily xanthine oxidase inhibitors. Allopurinol, which has been used to treat gout for six decades, is the first line urate-lowering therapy (ULT). However, the principles of ULT prescription, and allopurinol in particular have changed several times. Allopurinol remains the most widely used and highly effective drug in the world for lowering serum uric acid levels, and its prescription in routine clinical practice must fulfil several criteria.This article outlines the key principles of allopurinol therapy, including indications for use, treatment goals, dosing regimens, evaluation of efficacy, and use in elderly patients and patients with impaired renal function. Adherence to these principles will help prevent treatment failuresin gout and HU.